Лінгвокогнітивне дослідження порівняльних структур у німецькій мові. - Коропатніцька, Тетяна Петрівна (Науковий вісник Херсонського державного університету. Серія «Германістика та міжнародна комунікація» : збірник наукових праць. Херсон: ХДУ, 2020)
Purpose. The objective of this article is the analysis of the comparisons implemented with comparative structures with markers wie and als due to lingvo-cognitive parameters. The structure and comparison process is schematically presented in the form of a frame. The transition from the mental processes to the linear speech structure and the transition from linear verbal structure to a voluminous mental unit is modeled through a frame. Methods. Lingvo-cognitive analysis of the considered material involves the technique of multilevel conceptual networks modeling, developed due to the frame semantics. The move towards lingvo-cognitive methods is based on using frame modeling as a method of scientific-cognitive activity to represent comparison as a universal lingvo-cognitive model of knowledge in order to identify patterns of intellectual and verbal activity of the addressee. Using the frame, we form the move from mental processes in the recipient’s mind to a linear linguistic structure and from a linear verbal structure to a volumetric mental unit, which is the decoding of information in the process of which the linguistic structure goes through the formed by the recipient frame, unfolds and causes in his/her consciousness images and concepts.Results. The frame of comparison studied as a network model in the form of nodes and links between nodes (sentences) that are generated through propositional schemes. Depending on the feature category, these schemes have several variants: (1) quantitative scheme (comparison by quantitative parameter), (2) qualifying scheme (comparison by qualitative parameter), (3) scheme of the action (comparison by the actual parameter).The frame of comparison is represented by framed networks of similarity and differentiality. They are accordingly represented by the subframes of identity, similarity, likeness, equality and opposition, difference, incoherence, inequality, variation of which is formed by the certain characteristics of the situation of comparison: qualitative or quantitative feature is identified; the similarity depends on the subjective perception, or does not depend on the person; the concepts of one or several semantic fields are compared; static or dynamic characteristics are updated.Conclusions. The advantages of the lingvo-cognitive approach to the process of comparison are obvious, as it gives great prospects of this phenomenon in relation to a person, with his/her mental and cognitive processes in all connections with the surrounding world
Keywords: cognitive comparison operationcomparison processframe modellingframe of comparisoncognitive comparison models